2018
DOI: 10.5194/os-14-1021-2018
|View full text |Cite
|
Sign up to set email alerts
|

Downwelling surface solar irradiance in the tropical Atlantic Ocean: a comparison of re-analyses and satellite-derived data sets to PIRATA measurements

Abstract: This paper assesses the merits and drawbacks of several data sets of solar downwelling radiation received at the horizontal surface of the tropical Atlantic Ocean where the magnitude of this radiation and its spatial and temporal variability are not well known. The data sets are compared to quality-controlled measurements of hourly means of irradiance made at five buoys of the PIRATA network for the period 2012-2013. The data sets comprise the re-analyses MERRA-2 and ERA5, and three satellite-derived data sets… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 41 publications
5
24
2
Order By: Relevance
“…All Q net products have problems achieving a balanced energy budget at the ocean surface, with an overestimation of the downward heat input to the ocean ranging from 5 to 20 W m −2 (Yu, 2019). For reanalysis fluxes, there are major uncertainties in tropical shortwave and longwave radiation associated with the long-standing problems of parameterizing tropical convective clouds and low-altitude stratocumulus clouds in reanalysis models (Trolliet et al, 2018). For satellite fluxes, major uncertainties are related to turbulent bulk flux parameterization schemes and also satellite retrieval algorithms.…”
Section: Processes That Affect Upper-ocean Temperature and Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…All Q net products have problems achieving a balanced energy budget at the ocean surface, with an overestimation of the downward heat input to the ocean ranging from 5 to 20 W m −2 (Yu, 2019). For reanalysis fluxes, there are major uncertainties in tropical shortwave and longwave radiation associated with the long-standing problems of parameterizing tropical convective clouds and low-altitude stratocumulus clouds in reanalysis models (Trolliet et al, 2018). For satellite fluxes, major uncertainties are related to turbulent bulk flux parameterization schemes and also satellite retrieval algorithms.…”
Section: Processes That Affect Upper-ocean Temperature and Salinitymentioning
confidence: 99%
“…Gliders have already proven valuable for measuring upper-ocean turbulence and the factors that control it (St. Laurent and Merrifield, 2017). Satellite-based retrievals of surface radiative and turbulent fluxes show considerable skill (Yu and Weller, 2007;Trolliet et al, 2018) and are likely to improve further if satellite and in situ measurements are maintained.…”
Section: Strengths and Weaknesses Of The Current Observing Systemmentioning
confidence: 99%
“…Several meteorological reanalyses provide estimates of E for the entire world and span several decades back in time, such as ERA-Interim, ERA5, MERRA, and MERRA-2. Published validations of these reanalyses against measurements of E performed by instruments based inland or offshore found that the bias is not constant in space and reported that these reanalysis exhibits large standard deviation of errors (Bengulescu et al, 2017;Boilley and Wald, 2015;Jones et al, 2017;Trolliet et al, 2018). It is also reported that reanalyses often exhibit cloudy conditions while actual conditions are cloud-free and vice versa.…”
Section: Introductionmentioning
confidence: 97%
“…The downwelling solar radiation received at ground level is known to be an essential variable in many domains , including weather and climate, but also life on Earth for animals, plants (Bois et al, 2008;Colombo et al, 2009;Wagner et al, 2012) and humans (Juzeniene et al, 2011), or solar energy. The solar irradiance E is the density of power received from the sun on a horizontal surface at ground level and per unit surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation